Investigation the rate of Social Media Dependency among Undergraduate Medical School University Students in Ardabil city, Iran - Roya Motavalli; Serap Ejder Apay; Fatmazehra Akpinar Selvasli; Laleh Mahmoudnejad; Somayyeh Nouri (Patient Safety and Quality Improvement Journal)
Introduction: Nowadays the most widely used applications on the Internet are social networks. It has been reported that excessive use of social media has a negative impact on physical and mental health by causing dependency. Main objective of this study was to investigate the rate of social media dependency among undergraduate medical school university students in Ardabil city, Iran. Materials and Methods: This cross-sectional descriptive-analytical study was conducted among department of medicine students to investigate the level of social media dependency from April 2023 to December 2023. A total of 540 people were participated in the study. The questionnaire along with the demographic information questionnaire was provided for the users and after collecting and scoring the questionnaires, the data were coded and then entered into the SPSS version 24 and then analyzed by descriptive statistics methods in the form of tables, graphs, statistical indicators like average and standard deviation. Furthermore, ANOVA test and Pearson's correlation coefficient were used to check the relationship between statistical data. Results: Of all students, 12.8% had strong dependence on social networks and 71.9% of them had moderate dependence. It was found that the level of dependence to social networks does not have a significant relationship with the students’ age, gender, the age of parents and the number of family members, but it has a significant relationship with the position (birth order) of children in the family and the field of study. It was observed that there is a negative relationship between the academic year of students and the level of dependency to social media. Conclusions: According to the results, it was determined that measures should be taken to inform students about the harmful effects of excessive and uncontrolled use of social media.